The English Teaching And Learning Process of MAN 1 Boyolali - Windrati, Windrati; , Prof. Dr. Endang Fauziati, M.Hum; , Dr. Anam Sutopo, M.Hum (2016)
THE ENGLISH TEACHING AND LEARNING PROCESS OF MAN 1 BOYOLALI by WINDRATI NIM. S 200110050 windratiirfani@yahoo.co.id ABSTRACT English as means as international communication in the world. It is world window to attain enormous knowledge. The existence of English teaching learning process is a current issue in senior high school. It is needed to face Asian Economic Community. The purposes of this study are expose briefly the English teaching learning process of MAN 1 Boyolali namely : learning objective, syllabus, classroom procedure, classroom technique, learning material, teacher and student's role, media, assessment and strength and weaknesses. The study was an micro ethnographic study. The result of research portrays learning objective categorized into general and specific outcome. The syllabus of research is mixed syllabus. It consist of functional, structural, lexical, genre based text and skill based syllabus. The classroom procedure is two pattern namely : BKOF-MOT-JCOT-ICOT and BKOF-MOT-ICOT. The classroom technique are mind mapping, brainstorming, think-pair-share, think-aloud pair problem solving, drilling, questioning, presenting, practicing, discussing, and concluding. The learning material is divided into printed for instance, handbook, worksheet , handout and and unprinted such as MP3 file, slide, cassette and CD room. The Student's role are as listener, an active participant, a processor, coordinator and problem solver. The teacher's role are a manager, guide and instructor, a guide and instructor and explainer. The media are language laboratory, laptop and LCD projector, internet and , speaker active. The assessment applied to written test such as dialogue completion task, multiple choice and listening close task. It also uses observation, portfolio and project in assessment. There are strength and weakness among English teaching learning process at MAN 1 Boyolali. Due to to finding , discussion, conclusion and implication, the writer suggests for English teacher to enlarge their knowledge and involves their student in classroom actively. The application of variety methods, model and technique are obviously needed in English teaching. The writer also recommends for future to inflate the study in other research field. Keywords: Teaching, Learning , Process